2016
DOI: 10.1080/14767058.2016.1210598
|View full text |Cite
|
Sign up to set email alerts
|

Sustained versus intermittent lung inflation for resuscitation of preterm infants: a randomized controlled trial

Abstract: Delivery room SLI is more effective than intermittent bag and mask inflation for improving short-term respiratory outcome in preterm infants, without significant adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 28 publications
7
40
0
Order By: Relevance
“…Sustained inflation is currently standard practice in parts of Europe 9 based on studies in animals, asphyxiated term infants, 4 and smaller human randomized clinical trials in both preterm and near-term infants. 7,8,[27][28][29][30][31][32][33][34][35] Previous studies showed a reduction in mechanical ventilation within the first 72 hours of life 27,28 in infants receiving sustained inflation. Two meta-analyses 7,8 found a short-term benefit of sustained inflation, but a Cochrane review 8 suggested caution in interpretation of pooled analyses, noting marked interstudy heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustained inflation is currently standard practice in parts of Europe 9 based on studies in animals, asphyxiated term infants, 4 and smaller human randomized clinical trials in both preterm and near-term infants. 7,8,[27][28][29][30][31][32][33][34][35] Previous studies showed a reduction in mechanical ventilation within the first 72 hours of life 27,28 in infants receiving sustained inflation. Two meta-analyses 7,8 found a short-term benefit of sustained inflation, but a Cochrane review 8 suggested caution in interpretation of pooled analyses, noting marked interstudy heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses 7,8 found a short-term benefit of sustained inflation, but a Cochrane review 8 suggested caution in interpretation of pooled analyses, noting marked interstudy heterogeneity. Prior smaller studies included more mature infants, 27,[31][32][33][34][35] involved shorter inspiratory durations, 29 reported surrogate outcomes, 29,35 had important co-interventions, 27 or were stopped early for futility. 30 This trial used sustained in-flations with peak pressures that were similar to prior studies 27,28,30 and durations similar to some.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical trials of SLI at birth in preterm infants have yielded conflicting results. In some studies, SLI significantly reduced the need for mechanical ventilation (MV), while other studies showed no reduction . A recent Cochrane review reported that there was insufficient evidence that SLI is superior to IPPV in terms of MV requirement and other important respiratory outcomes …”
Section: Introductionmentioning
confidence: 99%
“…Nearly all of the studies investigating the efficacy of SLI have used neonatal face‐masks as the interface . However, the use of neonatal face‐masks for both SLI and IPPV has been associated with significant air leakage or airway obstruction, thus reducing the effectiveness of the procedure .…”
Section: Introductionmentioning
confidence: 99%